Pragmatist ethics a problem-based approach to what matters - Liszka, James Jakób, 1950- (SUNY series in American philosophy and cultural thought, 2021)
"Argues that the path to the good life does not consist in working toward some abstract concept of the good, but rather by ameliorating the problems of the practices and institutions that make up our practical life"--